A Portrayal of a Woman’s Struggles And Self-Liberation in The Patriarchal System - Fajarini, Suzana (Faculty of Arts and Education, 2024)
This study aims to reveal the gender inequality undergone by the female character, and her struggles to unchained herself from the unfairness she experienced in the short story “Apa yang Paul McCartney Bisikkan di Telinga Janitra.” In the era where equality between man and woman becomes a daily issue, there is still no guarantee that a woman will easily be treated as equal as man. Career can be a sign that a woman has reached the more or less the same level as man, but in many cases, many women are forced to give up their career to take care of their family as men call it as the nature of women to be housewives and mothers. Feminist literary criticism is applied to examine the short story to reveal how the character struggles to release herself when she is clung by domestic patriarchal strong practice done by her husband. The result of the analysis reveals that the female character in the short story discussed is still portrayed to be only half-completely succeed to attain her freedom and equity against patriarchal confines. Keywords: feminist literary criticism, patriarchal system, struggle, unfairness